2019
DOI: 10.3103/s1063457619020047
|View full text |Cite
|
Sign up to set email alerts
|

Friction-Wear Behaviors of Chemical Vapor Deposited Diamond Films at High Temperatures

Abstract: Friction-wear behaviors of chemical vapor deposited diamond films at high temperaturesA diamond film was deposited on YT14 hard alloy cutting tool using a сhemical vapor deposition. The coefficients of friction and wear behaviors of the obtained diamond films at 500, 600, and 700 °C were investigated using a high temperature tribological tester. The results show that the C of diamond film is fully released at 700 °C, generating CO and CO 2 . The (220) plane of diamond film is oxidized fully at 500 °C, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Other abrasives also can be used for scratching such as silicates, nitrides, borides, aluminum oxides, CBN etc. It is again found that nucleation density decreases with the increase in particle size of the diamond abrasives [16][17][18]. So the particle size of the abrasives should be optimum and smaller in size are generally preferable.…”
Section: Introductionmentioning
confidence: 94%
“…Other abrasives also can be used for scratching such as silicates, nitrides, borides, aluminum oxides, CBN etc. It is again found that nucleation density decreases with the increase in particle size of the diamond abrasives [16][17][18]. So the particle size of the abrasives should be optimum and smaller in size are generally preferable.…”
Section: Introductionmentioning
confidence: 94%